Rising incidence of Pneumocystis pneumonia: A population-level descriptive ecological study in England. Issue 4 (April 2023) - Pates, Katharine; Periselneris, Jimstan; Russell, Mark D.; Mehra, Varun; Schelenz, Silke; Galloway, James B.
Summary: Objectives: Pneumocystis pneumonia (PCP) is an opportunistic infection that causes significant morbidity and mortality in the immunocompromised population. This population is growing and diversifying, yet contemporary epidemiology is lacking. We investigated the population-level incidence of PCP over the past decade. Methods: We conducted a descriptive study of all hospital admissions in England from April 2012 to March 2022. PCP episodes, age, median length of stay, gender and episodes of other respiratory fungal infections were collected. Consumption of Trimethoprim-Sulfamethoxazole was obtained between January 2019 and May 2022. Results: The incidence of PCP increased from 2·2–4·5/100, 000 population between 2012/2013 and 2019/2020 (p < 0·0001). There was a drop in 2020/2021 to 2·7/100, 000 before returning to 3.9/100, 000 in 2021/2022. PCP episodes rose as a proportion of all-cause admissions as well as a proportion of episodes due to other fungal infections. The proportion of PCP patients aged 75+ increased from 14% to 26%. The median length of stay was 13.5 days. Consumption of intravenous Trimethoprim-Sulfamethoxazole increased from 0.24 × 100, 000 to 0.30 × 100, 000 defined daily doses. Conclusions: The incidence of PCP is rising rapidly and represents a significant burden to the healthcare system. Further study into who is at risk of PCP is needed to better determine who should be given prophylaxis.